Reference service in academic libraries future trends : a Delphi study - Vijayan Narayananayar (2009)
IT and digitalisation are bringing about changes and challenges all over the world. This is also true in the case of Singapore. The library is one such institution which is undergoing many changes and is facing many challenges.